The Americans the democratic experience - Boorstin, Daniel J. (Daniel Joseph) 1914-2004
'Mr. Boorstin tells the story of the invention of a new democratic culture and the reorientation of the national character through countless little revolutions in economy, technology, and social rearrangements. Illuminated by reflections that are original, judicious and sagacious.'